Deviations of the centre of feet pressure in girls with scoliosis and scoliotic posture - Wilczyński Wilczyński; Michał Jerzy Paprocki; Katarzyna Wilczyńska; Igor Wilczyński (Kazimierz Wielki University, 2017)
Introduction. The aim of the research was to analyze selected deviations of the centre of feet pressure (COP) in girls with scoliosis and scoliotic posture. Material and methods. 28 girls aged 7-18 years old were involved in the study. Spine research was made by  Exhibeon digital radiography. Based on the size of the angle of spinal curvature there were identified scoliotic posture: 1-9° and scoliosis: ≥10°.  The deviations of the centre of feet pressure were examined by static-dynamic Tecnobody's ST 310 Plus Stability System platform. Results. Forward-Backward Standard Deviation Y was from 6,57 with opened eyes (OE) to 7,32 with closed eyes (CE). The difference in Romberg's Test was 0,75. Medium-Lateral Standard Deviation X was from 3,89 with opened eyes (OE) to 5,54 with closed eyes (CE). The difference in Romberg's Test was 1,65. Average Forward-Backward Speed Y was from 11,96 with opened eyes (OE) to 17,29 with closed eyes (CE). The difference in Romberg's Test was 5,33. Average Medium-Lateral Speed X was from 9,96 with opened eyes (OE) to 13,89 with closed eyes (CE). The difference in Romberg's Test was 3,93. Conclusion. In a study with closed eyes (CE)  it has been observed a significant increase of the centre of feet pressure deviations for: Medium-Lateral Standard Deviation X (p=0,022162), Average Forward-Backward Speed Y (p=0,000071) and Average Medium-Lateral Speed X (p=0,000916). Correlation analysis of the centre of feet pressure deviations with age demonstrated an important connections only in case of Medium-Lateral Standard Deviation X (r= -0,38, p=0,043).